A Role for Nuclear Actin in HDAC 1 and 2 Regulation - Serebryannyy, Leonid A. (Sci Rep, 2016)
Class I histone deacetylases (HDACs) are known to remove acetyl groups from histone tails. This liberates positive charges on the histone tail and allows for tighter winding of DNA, preventing transcription factor binding and gene activation. Although the functions of HDAC proteins are becoming apparent both biochemically and clinically, how this class of proteins is regulated remains poorly understood. We identified a novel interaction between nuclear actin and HDAC 1 and HDAC 2. Nuclear actin has been previously shown to interact with a growing list of nuclear proteins including chromatin remodeling complexes, transcription factors and RNA polymerases. We find that monomeric actin is able to bind the class I HDAC complex. Furthermore, increasing the concentration of actin in HeLa nuclear extracts was able to suppress overall HDAC function. Conversely, polymerizing nuclear actin increased HDAC activity and decreased histone acetylation. Moreover, the interaction between class I HDACs and nuclear actin was found to be activity dependent. Together, our data suggest nuclear actin is able to regulate HDAC 1 and 2 activity.